Integrated continuous-time filters principles, design, and applications - Tsividis, Y.P; Voorman, J.O (IEEE Press, 1993)
This book is a good collection of IEEE articles that deal with various methods of designing analog filters. What is nice about this text is that balanced as well as single ended circuits are explored. A significant number of articles dealing with Transconductance-C and MOSFET-C filter design is included. Bipolar and MOSFET filters are explained throughly.